2014
DOI: 10.1094/asbcj-2014-0114-01
|View full text |Cite
|
Sign up to set email alerts
|

A Curative Method for Primary Gushing of Beer and Carbonated Beverages: Characterization and Application of Antifoam Based on Hop Oils

Abstract: J. Am. Soc. Brew. Chem. 72(1): [12][13][14][15][16][17][18][19][20][21] 2014 Gushing is the vigorous overfoaming of carbonated beverages when the bottle is opened. Primary gushing in beer is mostly caused by a group of proteins called hydrophobins secreted by filamentous fungi, which contaminate CO 2 gaseous molecules during carbonation and form nanobubbles. The influence of hop oil antifoam on primary gushing showed a complete suppressing effect in sparkling water, a decreasing effect in wort, and no influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Hop extracts are commonly used in brewing in order to control the foam in boiling kettles and fermenters. Adding such an extract before carbonation is effective for gushing reduction [68]. The extract addition has a better effect when added to wort after cooling, and before fermentation.…”
Section: Hop Compoundsmentioning
confidence: 99%
“…Hop extracts are commonly used in brewing in order to control the foam in boiling kettles and fermenters. Adding such an extract before carbonation is effective for gushing reduction [68]. The extract addition has a better effect when added to wort after cooling, and before fermentation.…”
Section: Hop Compoundsmentioning
confidence: 99%
“…The major components of the hop extract are waxes (C29 and C31) which are strong gushing inducers (Shokribousjein et al, 2014) while some unsaturated fatty acids were gushing inhibitors. Based on the total amount of individual molecules in the hop extract, it is found that the majority of the molecules are gushing inducers.…”
Section: Gas Chromatography/mass Spectrometrymentioning
confidence: 99%
“…Such extract is a suitable alternative in order to decrease gushing and the result showed that it decreases gushing of beer when it is added before carbonation (Shokribousjein et al, 2014). The extract creates an interface in wort with which hydrophobins interact and further contact with gaseous CO 2 is inhibited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hop extracts usually used in breweries for possessing the specific tastes and aroma (Shokribousjein et al, ; ). The acidic constituents of the hop plant ( Humulus lupulus ) not only elicit bitter taste but also have antimicrobial activity against a wide spectrum of food spoilage bacteria such as Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%